FAKTOR RISIKO CARPAL TUNNEL SYNDROME PADA SISWA SEKOLAH MENENGAH ATAS PEMAIN GAME ONLINE DI KOTA DENPASAR - Pramandani, Ni Luh Made Susanthi; Wirawan, I Made Ady (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021, 2021)
ABSTRACT Carpal Tunnel Syndrome (CTS) is one of the disorders in the arm of the hand due to the narrowing of the carpal tunnel so that it occurs with an emphasis on the median nerve. Hand movements when using the keyboard and mouse in playing online games have a high repetition rate that affect the incidence of CTS. This research aimed to determine proportion and risk factors of CTS experienced by senior high students who playing game online in Denpasar city, using quantitative analytic research with cross-sectional study design. Respondents in this study amounted to 70 students with purposive sampling technique. The results showing CTS proportion of respondents at 31.43% in mild category. All individual characteristic variables including age (p=0.25) and gender (p=0.50) are not significantly related to CTS, while playing patterns, playing devices, and repetitive motion (p=0.00) are significantly related with CTS incidence. Playing patterns are the most influential risk factor of CTS incident in senior high students who play online game (OR = 23.74). Therefore government support in preventive – rehabilitative program for gamers addicted is necessary to educate students and their parents about game online’s impact.   Keywords: Carpal Tunnel Syndrome, Students, Game Online